A key management scheme for heterogeneous sensor networks using keyed-hash chain - Tian, Biming (IEEE, 2009)
We present a suite of key management scheme for heterogeneous sensor networks. In view of different types of communications, a single key can not satisfy various communication requirements. It is necessary to study the establishment and renewal of different types of keys in heterogeneous sensornetworks. In this paper, we propose a new key management scheme which can support five types of communications. Our basic scheme is based on a keyed-hash chain approach. A new cluster mechanism is used to improve the probability of key sharing between sensors and their cluster heads. Different from existing schemes where a node capture attack might lead to the disclosure of several key chains, our method can avoid this drawback through not storing network-wide generating keys inlow-cost sensors. Only pairwise keys involving the compromised node should be deleted in our scheme. It is motivated by the observation that all the information stored on a sensor may be disclosed once the sensor gets compromised. Through the analysis of both security and performance, we show the scheme meets the security requirements.